Enhanced Electrochemiluminescence from Ruthenium-Tagged Immune Complex at Flexible Chains for Sensitive Analysis of Glutamate Decarboxylase Antibody - Yuyao Zhang; Li Qian; Qian Zhang; Yu Li; Yu Liu; Dechen Jiang (Biosensors)
Herein, a sensitive electrochemiluminescence (ECL) immunosensor is designed by immobilizing ruthenium-tagged immune complexes at flexible poly-ethylene-glycol (PEG) chains on the electrode surface, which offers more freedom for the collision of the ruthenium complex at the electrode during the initial ECL reaction. The electrochemical characterizations confirm the loose structure of the assembled layer with the immune complex, providing an increase in the current and the resultant enhanced ECL emissions. Comparing the sensors with the rigid structure, a 34-fold increase in the maximal ECL emission is recorded when PEG3400 is used as a linker. Using the optimized protocol, the prepared immunosensor exhibits a wide-ranging linear response to the model antibody (glutamate decarboxylase antibody) ranging from 10 pg/mL to 10 ng/mL. The detection limit is almost two orders lower than the value using the classic enzyme-linked immunosorbent assay, which offers a new design to enhance ECL emissions and the resultant analytical performance.